Palladium (II) compounds containing oximes as promising antitumor agents for the treatment of osteosarcoma: An in vitro and in vivo comparative study with cisplatin - Pereira, Thales Hebert Regiani; de Moura, Thales Reggiani [UNESP]; Santos, Michele Rosana Maia; Zamarioli, Lucas dos Santos; Erustes, Adolfo G.; Smaili, Soraya S.; Pereira, Gustavo J.S.; Godoy Netto, Adelino Vieira de [UNESP]; Bincoletto, Claudia (Elsevier, 2024)
Drug resistance, evasion of cell death and metastasis are factors that contribute to the low cure rate and disease-free survival in osteosarcomas (OS). In this study, we demonstrated that a new class of oxime-containing organometallic complexes called Pd-BPO (O3) and Pd-BMO (O4) are more cytotoxic than cisplatin (CDDP) for SaOS-2 and U2OS cells using the MTT assay. Annexin-FITC/7-AAD staining demonstrated a greater potential for palladium-oxime complexes to induce death in SaOS-2 cells than CDDP, an event confirmed using the pan-caspase inhibitor Z-VAD-FMK. Compared to CDDP, only palladium-oxime complexes eradicated the clonogenicity of SaOS-2 cells after 7 days of treatment. The involvement of the lysosome-mitochondria axis in the cell death-inducing properties of the complexes was also evaluated. Using LysoTracker Red to label the acidic organelles of SaOS-2 cells treated with the O3 and O4 complexes, a decrease in the fluorescence intensity of this probe was observed in relation to CDDP and the control. Lysosomal membrane permeabilization (LMP) was also induced by the O3 and O4 complexes in an assay using acridine orange (A/O). The greater efficiency of the complexes in depolarizing the mitochondrial membrane compared to SaOS-2 cells treated with CDDP was also observed using TMRE (tetramethyl rhodamine, ethyl ester). For in vivo studies, C. elegans was used and demonstrated that both complexes reduce body bends and pharyngeal pumping after 24 h of treatment to the same extent as CDDP. We conclude that both palladium-oxime complexes are more effective than CDDP in inducing tumor cell death. The toxicity of these complexes to C. elegans was like that induced by CDDP. These results encourage preclinical studies aimed at developing more effective drugs for the treatment of osteosarcoma (OS). Furthermore, we propose palladium-oxime complexes as a new class of antineoplastic agents.
Keywords: C. elegans; Cell death; Cyclopalladated; Lysosomes; Mitochondria; Osteosarcoma; Oximes